Laminated common mode filter and manufacturing method thereof
By setting a non-magnetic layer in the stacked common mode filter, the stress of the magnetic layer is offset by using non-magnetic CuZn ferrite material during the sintering process, the internal cracks and cracking problems caused by sintering stress are solved, the magnet reliability of the product is improved and the process is simplified.
Patent Information
- Application Number
- CN202411739021.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-04
AI Technical Summary
During the sintering process, the sintering shrinkage curves of magnetic materials and non-magnetic materials are inconsistent, resulting in internal stress accumulation, internal cracks and interlayer cracks, affecting the product's magnet reliability.
A non-magnetic layer is provided on the side of the magnetic layer away from the intermediate non-magnetic layer. The materials of the non-magnetic layer and the intermediate non-magnetic layer are non-magnetic CuZn ferrite materials. Through this laminated structure, the stress of the intermediate non-magnetic layer to the magnetic layer and the stress of the non-magnetic layer to the magnetic layer are canceled out from each other during the sintering process, thereby improving the sintering stress.
It effectively avoids internal cracks and cracks, improves the product's magnet reliability, while simplifying the process and reducing costs.
Smart Images

Figure CN119763982A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of power devices, and in particular to a laminated common mode filter and a manufacturing method thereof. Background Art
[0002] The application background of laminated common mode filters mainly stems from the demand for high-speed data transmission in modern electronic devices and the resulting common mode noise problem. With the improvement of screen resolution and camera pixels of devices such as smartphones and tablets, as well as the popularization of 5G technology, the transmission speed of electronic devices has been greatly improved, but it has also brought more high-frequency common mode noise interference. Common mode inductors, as an effective way to solve high-frequency common mode interference, are widely used in data transmission interfaces of various common electronic products, such as MIP I, HDMI, USB, etc., to filter out common mode noise and suppress electromagnetic wave radiation and external electromagnetic interference. As an advanced EMI filter, laminated common mode filters can provide lower differential mode loss and more effectively solve RF I / EMI noise interference problems through their special design and structure, and are suitable for a variety of electronic devices.
[0003] Laminated common mode filters are generally composed of non-magnetic material layers, magnetic material layers and silver electrodes. During the sintering process, the non-magnetic material will first complete the contraction at a temperature of 650°C to 800°C, and the magnetic material will only contract between 800°C and 900°C. At this time, the contraction of the magnetic material will be restricted by the non-magnetic material that can no longer contract, resulting in internal stress. When the stress accumulates to a certain extent, it will cause cracks inside the magnet and even interlayer cracking. The existing way to solve this problem is to make the sintering shrinkage curves of the magnetic material and the non-magnetic material as consistent as possible to promote synchronous co-firing. However, the sintering shrinkage between different functional materials is quite different, and the research progress of synchronous sintering shrinkage is relatively slow. Internal cracks and cracking have also become one of the problems that plague the mass production of laminated common mode filters. Summary of the invention
[0004] The first object of the present invention is to provide a laminated common mode filter which can improve sintering stress, avoid internal cracks and cracks, and improve the magnetic reliability of the product.
[0005] A second object of the present invention is to provide a method for manufacturing the above-mentioned laminated common mode filter.
[0006] To achieve the above-mentioned first purpose, the present invention provides a laminated common mode filter, comprising a first magnetic layer, a second magnetic layer, an intermediate non-magnetic layer and an internal electrode; the first magnetic layer, the intermediate non-magnetic layer and the second magnetic layer are stacked in sequence, and the internal electrode is located in the intermediate non-magnetic layer; the laminated common mode filter also includes a first non-magnetic layer and a second non-magnetic layer; the first non-magnetic layer is arranged on a side of the first magnetic layer away from the intermediate non-magnetic layer, and the second non-magnetic layer is arranged on a side of the second magnetic layer away from the intermediate non-magnetic layer; the materials of the first non-magnetic layer, the second non-magnetic layer and the intermediate non-magnetic layer are all non-magnetic CuZn ferrite materials.
[0007] It can be seen from the above scheme that by setting a non-magnetic layer on the side of the magnetic layer away from the intermediate non-magnetic layer, the materials of the non-magnetic layer and the intermediate non-magnetic layer are both non-magnetic CuZn ferrite materials. Therefore, during the sintering process, the stress of the intermediate non-magnetic layer on the first magnetic layer and the stress of the first non-magnetic layer on the first magnetic layer can completely offset or partially offset each other, and the stress of the intermediate non-magnetic layer on the second magnetic layer and the stress of the second non-magnetic layer on the second magnetic layer can completely offset or partially offset each other, so the sintering stress can be improved, internal cracks and cracking can be avoided, and the magnet reliability of the product can be improved. At the same time, the first non-magnetic layer and the second non-magnetic layer can be made of the same material as the intermediate non-magnetic layer, which can simplify the process and reduce costs.
[0008] A preferred solution is that the materials of the first magnetic layer and the second magnetic layer are both NiZnCu ferrite materials.
[0009] A preferred solution is that the materials of the first non-magnetic layer, the second non-magnetic layer and the intermediate non-magnetic layer are all non-magnetic CuZn ferrite materials with a spinel structure.
[0010] In a preferred embodiment, the ratio of the thickness of the first non-magnetic layer to the thickness of the first magnetic layer is in the range of 0.1 to 1.
[0011] It can be seen that when the thickness ratio of the first non-magnetic layer to the adjacent first magnetic layer is less than 0.1, during the device sintering process, the stress of the first non-magnetic layer on the first magnetic layer is difficult to completely offset the stress of the non-magnetic layer on the first magnetic layer, and cracks may occur inside the product. After the chamfering process, the cracks extend to the outside of the product and cracking occurs. When the thickness ratio of the first non-magnetic layer to the first magnetic layer is greater than 1 while the total thickness of the product remains unchanged, the thickness of the magnetic layer is relatively reduced, resulting in a decrease in the inductance of the product, which does not meet the electrical use requirements of the product.
[0012] According to a further solution, a ratio of the thickness of the first non-magnetic layer to the thickness of the first magnetic layer is in a range of 0.14 to 0.45.
[0013] It can be seen that when the ratio of the thickness of the first non-magnetic layer to the first magnetic layer is in the range of 0.14 to 0.45, it can ensure that the sintering stress is improved and internal cracks and cracks are avoided, while ensuring that the product has good performance.
[0014] In a preferred embodiment, the ratio of the thickness of the second non-magnetic layer to the thickness of the second magnetic layer is in the range of 0.1 to 1.
[0015] According to a further embodiment, a ratio of the thickness of the second non-magnetic layer to the thickness of the second magnetic layer is in a range of 0.14 to 0.45.
[0016] A preferred solution is that the thickness of the first non-magnetic layer and the second non-magnetic layer are both in the range of 17um to 43um, and the thickness of the first magnetic layer and the second magnetic layer are both in the range of 96um to 120um.
[0017] A preferred solution is that the first non-magnetic layer is located at the top layer of the laminated common mode filter, and the second non-magnetic layer is located at the bottom layer of the laminated common mode filter.
[0018] To achieve the above-mentioned second purpose, the present invention provides a method for manufacturing the above-mentioned laminated common mode filter, the manufacturing method comprising: step one, preparing magnetic ferrite slurry and non-magnetic ferrite slurry; step two, respectively casting the magnetic ferrite slurry and the non-magnetic ferrite slurry on a PET film to prepare a magnetic ferrite green tape and a non-magnetic ferrite green tape, each of which is cut into a single-layer green tape, and an electrode pattern is made on a part of the non-magnetic ferrite green tape to form an intermediate non-magnetic layer; step three, subjecting the non-magnetic ferrite green tape without an electrode pattern printed thereon, the magnetic ferrite green tape and the non-magnetic ferrite green tape printed thereon with an electrode pattern to a lamination process, and stacking and pressing the green tapes layer by layer in the order of the non-magnetic ferrite green tape without an electrode pattern printed thereon, the magnetic ferrite green tape, the non-magnetic ferrite green tape printed thereon with an electrode pattern printed thereon, the magnetic ferrite green tape and the non-magnetic ferrite green tape without an electrode pattern printed thereon.
[0019] It can be seen from the above scheme that by setting a non-magnetic layer on the side of the magnetic layer away from the intermediate non-magnetic layer, the non-magnetic layer and the intermediate non-magnetic layer are made of the same material, both of which are non-magnetic CuZn ferrite materials with a spinel structure. Therefore, during the sintering process, the stress of the intermediate non-magnetic layer on the first magnetic layer and the stress of the first non-magnetic layer on the first magnetic layer can completely offset or partially offset each other, and the stress of the intermediate non-magnetic layer on the second magnetic layer and the stress of the second non-magnetic layer on the second magnetic layer can completely offset or partially offset each other, so the sintering stress can be improved, internal cracks and cracking can be avoided, and the magnet reliability of the product can be improved. At the same time, the first non-magnetic layer and the second non-magnetic layer use the same material as the intermediate non-magnetic layer, which can simplify the formula, simplify the process, and reduce costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic structural diagram of an embodiment of a laminated common mode filter of the present invention.
[0021] The present invention is further described below in conjunction with the accompanying drawings and embodiments. DETAILED DESCRIPTION
[0022] See also Figure 1 The laminated common mode filter of this embodiment includes a first magnetic layer 1, a second magnetic layer 2, an intermediate non-magnetic layer 3, a first non-magnetic layer 4, a second non-magnetic layer 5, an inner electrode 6 and an outer electrode (not shown).
[0023] The first non-magnetic layer 4 is located at the top layer of the laminated common mode filter, the second non-magnetic layer 5 is located at the bottom layer of the laminated common mode filter, and the first non-magnetic layer 4, the first magnetic layer 1, the intermediate non-magnetic layer 3, the second magnetic layer 2 and the second non-magnetic layer 5 are stacked in sequence, the inner electrode 6 is located in the intermediate non-magnetic layer 3, and the outer electrode is arranged on the outer surface of the laminated common mode filter and is electrically connected to the inner electrode 6.
[0024] The materials of the first non-magnetic layer 4, the second non-magnetic layer 5 and the intermediate non-magnetic layer 3 are the same and are all non-magnetic CuZn ferrite materials with a spinel structure. The materials of the first magnetic layer 1 and the second magnetic layer 2 are all NiZnCu ferrite materials.
[0025] The ratio of the thickness of the first non-magnetic layer 4 to the first magnetic layer 1 is in the range of 0.1 to 1, and the ratio of the thickness of the second non-magnetic layer 5 to the second magnetic layer 2 is in the range of 0.1 to 1. Preferably, the ratio of the thickness of the first non-magnetic layer 4 to the first magnetic layer 1 is in the range of 0.14 to 0.45, the ratio of the thickness of the second non-magnetic layer 5 to the second magnetic layer 2 is in the range of 0.14 to 0.45, the thickness of the first non-magnetic layer 4 and the second non-magnetic layer 5 are both in the range of 17um to 43um, and the thickness of the first magnetic layer 1 and the second magnetic layer 2 are both in the range of 96um to 120um.
[0026] When the thickness ratio of the first non-magnetic layer 4 to the adjacent first magnetic layer 1 is less than 0.1, during the device sintering process, the stress of the first non-magnetic layer 4 on the first magnetic layer 1 is difficult to completely offset the stress of the non-magnetic layer on the first magnetic layer 1, and cracks may occur inside the product. After the chamfering process, the cracks extend to the outside of the product, causing cracking. When the thickness ratio of the first non-magnetic layer 4 to the first magnetic layer 1 is greater than 1 while the total thickness of the product remains unchanged, the thickness of the magnetic layer is relatively reduced, resulting in a decrease in the inductance of the product, which does not meet the electrical use requirements of the product.
[0027] The manufacturing method of the above-mentioned laminated common mode filter comprises the following steps:
[0028] Step 1: According to different formula ratios, magnetic ferrite powder and non-magnetic ferrite powder are mixed with organic solvents respectively, and magnetic ferrite slurry and non-magnetic ferrite slurry with a certain viscosity are prepared after stirring and grinding.
[0029] In step 2, magnetic ferrite slurry and non-magnetic ferrite slurry are respectively cast on PET film to prepare magnetic ferrite green tape and non-magnetic ferrite green tape, each of which is cut into a single-layer green tape, and an electrode pattern is made on part of the non-magnetic ferrite green tape to form an intermediate non-magnetic layer 3.
[0030] Step 3: The non-magnetic ferrite green tape without the printed electrode pattern, the magnetic ferrite green tape and the non-magnetic ferrite green tape with the printed electrode pattern are subjected to a lamination process, and the green tapes are stacked and pressed layer by layer in the order of the non-magnetic ferrite green tape without the printed electrode pattern, the magnetic ferrite green tape, the non-magnetic ferrite green tape with the printed electrode pattern, the magnetic ferrite green tape and the non-magnetic ferrite green tape without the printed electrode pattern to form a green body. At this time, the thickness of the first non-magnetic layer 4 and the second non-magnetic layer 5 are both in the range of 40um to 60um, and the thickness of the first magnetic layer 1 and the second magnetic layer 2 are both in the range of 120um to 150um, and the thickness ratio of the first non-magnetic layer 4 to the first magnetic layer 1 and the thickness ratio of the second non-magnetic layer 5 to the second magnetic layer 2 are both in the range of 0.26 to 0.50.
[0031] Step four, cutting, debinding and sintering the green body formed in step three to form a semi-finished product after sintering. In the semi-finished product, the thickness of the first non-magnetic layer 4 and the second non-magnetic layer 5 are both in the range of 32um to 48um, and the thickness of the first magnetic layer 1 and the second magnetic layer 2 are both in the range of 96um to 120um, and the thickness ratio of the first non-magnetic layer 4 to the first magnetic layer 1 and the thickness ratio of the second non-magnetic layer 5 to the second magnetic layer 2 are both in the range of 0.26 to 0.50.
[0032] Step 5: Chamfer the semi-finished product formed in step 4, and the thickness of the first non-magnetic layer 4 and the second non-magnetic layer 5 are both reduced by 5um to 15um. At this time, the thickness of the first non-magnetic layer 4 and the second non-magnetic layer 5 are both in the range of 17um to 43um, the thickness of the first magnetic layer 1 and the second magnetic layer 2 are both in the range of 96um to 120um, and the thickness ratio of the first non-magnetic layer 4 to the first magnetic layer 1 and the thickness ratio of the second non-magnetic layer 5 to the second magnetic layer 2 are both in the range of 0.14 to 0.45.
[0033] Step 6: The product obtained in step 5 is subjected to processes such as silver dipping, electroplating, and testing to produce a single product. The thickness of the first non-magnetic layer 4 and the second non-magnetic layer 5 in the finished product is in the range of 17um to 43um, the thickness of the first magnetic layer 1 and the second magnetic layer 2 is in the range of 96um to 120um, and the ratio of the thickness of the first non-magnetic layer 4 to the first magnetic layer 1 and the ratio of the thickness of the second non-magnetic layer 5 to the second magnetic layer 2 are in the range of 0.14 to 0.45.
[0034] As can be seen from the above, by adding two non-magnetic layers, the first magnetic layer is sandwiched between the first non-magnetic layer and the middle non-magnetic layer, and the second magnetic layer is sandwiched between the second non-magnetic layer and the middle non-magnetic layer. The non-magnetic layer and the middle non-magnetic layer are made of the same material, both of which are non-magnetic CuZn ferrite materials with a spinel structure. Therefore, during the sintering process, the stress of the middle non-magnetic layer on the first magnetic layer and the stress of the first non-magnetic layer on the first magnetic layer can completely offset or partially offset each other, and the stress of the middle non-magnetic layer on the second magnetic layer and the stress of the second non-magnetic layer on the second magnetic layer can completely offset or partially offset each other, so the sintering stress can be improved, internal cracks and cracking can be avoided, the magnet reliability of the product can be improved, the mass production efficiency can be further improved, and the production cost can be reduced. At the same time, the first non-magnetic layer and the second non-magnetic layer use the same material as the middle non-magnetic layer, which can simplify the formula, simplify the process, and reduce costs.
[0035] Finally, it should be emphasized that the above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A laminated common mode filter comprising a first magnetic layer, a second magnetic layer, an intermediate non-magnetic layer and an inner electrode; The first magnetic layer, the middle non-magnetic layer and the second magnetic layer are stacked in sequence, and the inner electrode is located in the middle non-magnetic layer; Features: The laminated common mode filter also includes a first non-magnetic layer and a second non-magnetic layer; The first non-magnetic layer is arranged on a side of the first magnetic layer away from the intermediate non-magnetic layer, and the second non-magnetic layer is arranged on a side of the second magnetic layer away from the intermediate non-magnetic layer; The materials of the first non-magnetic layer, the second non-magnetic layer and the intermediate non-magnetic layer are all non-magnetic CuZn ferrite materials.
2. The laminated common mode filter according to claim 1, characterized in that: The first magnetic layer and the second magnetic layer are both made of NiZnCu ferrite material.
3. The laminated common mode filter according to claim 1, characterized in that: The materials of the first non-magnetic layer, the second non-magnetic layer and the intermediate non-magnetic layer are all non-magnetic CuZn ferrite materials with a spinel structure.
4. The laminated common mode filter according to any one of claims 1 to 3, characterized in that: A ratio of the thickness of the first non-magnetic layer to the first magnetic layer is in the range of 0.1 to 1.
5. The laminated common mode filter according to claim 4, characterized in that: A ratio of the thickness of the first non-magnetic layer to the first magnetic layer is in a range of 0.14 to 0.
45.
6. The laminated common mode filter according to any one of claims 1 to 3, characterized in that: A ratio of the thickness of the second non-magnetic layer to the second magnetic layer is in the range of 0.1 to 1.
7. The laminated common mode filter according to claim 6, characterized in that: A ratio of the thickness of the second non-magnetic layer to the second magnetic layer is in a range of 0.14 to 0.
45.
8. The laminated common mode filter according to any one of claims 1 to 3, characterized in that: The thickness of the first non-magnetic layer and the second non-magnetic layer are both in the range of 17um to 43um, and the thickness of the first magnetic layer and the second magnetic layer are both in the range of 96um to 120um.
9. The laminated common mode filter according to any one of claims 1 to 3, characterized in that: The first non-magnetic layer is located on the top layer of the laminated common mode filter, and the second non-magnetic layer is located on the bottom layer of the laminated common mode filter.
10. A method for manufacturing a laminated common mode filter, characterized in that: A laminated common mode filter according to any one of claims 1 to 9 is manufactured, wherein the manufacturing method comprises: Step 1, preparing magnetic ferrite slurry and non-magnetic ferrite slurry; Step 2: Magnetic ferrite slurry and non-magnetic ferrite slurry are respectively cast on PET film to prepare magnetic ferrite green tape and non-magnetic ferrite green tape, each of which is cut into a single-layer green tape, and an electrode pattern is made on part of the non-magnetic ferrite green tape to form the intermediate non-magnetic layer; Step three, subjecting the non-magnetic ferrite green tape without printed electrode pattern, the magnetic ferrite green tape and the non-magnetic ferrite green tape with printed electrode pattern to a lamination process, and stacking and pressing the green tapes layer by layer in the order of the non-magnetic ferrite green tape without printed electrode pattern, the magnetic ferrite green tape, the non-magnetic ferrite green tape with printed electrode pattern, the magnetic ferrite green tape and the non-magnetic ferrite green tape without printed electrode pattern.